A multicenter, single‐group, open feasibility study of a new individual cognitive behavioral therapy program for adult Japanese patients with attention‐deficit/hyperactivity disorder: Study protocol - Naoki Takamatsu; Misuzu Nakashima; Kei Matsuura; Ikue Umemoto; Masaya Ito; Junichiro Kanazawa; Hirofumi Tomiyama; Masaki Kondo; Hisateru Tachimori; Tomohiro Nakao; Masaru Horikoshi; Hironori Kuga (PCN Reports)
Abstract Background Attention‐deficit/hyperactivity disorder (ADHD) symptoms, including executive function, emotional regulation, and motivation, can persist into adulthood and are often associated with mental illnesses. Cognitive behavioral therapy (CBT) may help ADHD adults in Japan, but the lack of studies and the variability in group CBT approaches make its effects unclear. Japan lacks unified CBT programs and adult ADHD guidelines, making it difficult to implement international individual CBT recommendations due to cultural differences. This study will assess the feasibility of a novel CBT program for Japanese adult ADHD patients. Methods This feasibility study will be open, nonrandomized, single‐arm, multicenter study. Twelve ADHD patients aged 20–65 years who are currently receiving treatment will be included based on Conners' Adult ADHD Rating Scale (CAARS) clinical severity threshold. An intervention phase of 12–16 weeks and a 12‐week follow‐up will total 24–28 weeks for all participants. The intervention will use a new CBT program tailored to individual assessments. Results The primary objective is to determine feasibility using dropout rates, adverse events, and CAARS score changes between Weeks 1 and 16. The secondary outcomes will assess long‐term effects of treatment beyond the intervention period and provide descriptive statistics on sex, depression, quality of life, and autistic scores in relation to the intervention outcomes. The full analysis set and per protocol set will be used for statistical analysis. Conclusions This study is essential for the development of CBT interventions in accordance with Japan's healthcare system that are tailored to the unique needs of its population.